1999
DOI: 10.1063/1.369413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hole transport layer on the performance of organic light-emitting diodes

Abstract: We investigate the influence of the hole-transporting layer ͑HTL͒ on the performance of bilayer vapor-deposited organic light-emitting diodes. Three different HTL materials were used: m-MTDATA, triphenyl-diamine, and naphthyl-phenyl-diamine. In all cases, Alq 3 was the electron-transporting layer ͑ETL͒. We measure and compare the current density-voltage (J -V) and luminance-voltage ͑L-V͒ characteristics of these devices and we conclude that the operating voltage is controlled by the type of HTL used and the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
78
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 24 publications
2
78
1
Order By: Relevance
“…However, it has been shown that the OLED quantum efficiency is independent of the HTL mobility. 8 Finally, it has been shown that exciplex formation between the HTL and the emission layer reduces the device efficiency, 6 however we find no evidence of exciplex emission in these devices.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…However, it has been shown that the OLED quantum efficiency is independent of the HTL mobility. 8 Finally, it has been shown that exciplex formation between the HTL and the emission layer reduces the device efficiency, 6 however we find no evidence of exciplex emission in these devices.…”
contrasting
confidence: 45%
“…5,6 However, more recent studies have shown that the device quantum efficiency increases as the difference between the IP of the HTL and the emission layer is decreased. 7,8 These studies have generally been done using thermally deposited small-molecule hole transport materials. One disadvantage to this approach is that the morphological properties of the HTL film are affected by the particular molecular design.…”
mentioning
confidence: 99%
“…It has been suggested that the enhanced performance in HIL/HTL devices is due to a sequence of cascaded hole-injection barriers present in the HIL/HTL/ETL structure, which produces a "balanced" electron-hole recombination at the HTL/ETL interface. 12,13 In this paper, we systematically investigate the effect of the HIL on OLED performance characteristics, specifically the cause for current efficiency enhancement. Figure 1 shows the multilayer OLED structure and the molecular structures for the HIL ͑MTDATA͒, HTL ͑NPB͒, and ETL ͑Alq͒.…”
mentioning
confidence: 99%
“…Because the fraction of radiative exciplex recombination 7 is small, the appearance of exciplexes generally lowers the efficiency of OLEDs. Exciplex related investigations in OLEDs have also been conducted in relation to aging: Giebeler et al 7 considered the effects of heat or electrical stress on exciplex emitting OLEDs and found a reduction of exciplex emission as a function of time. In another paper, 8 exciplex emission was used to estimate the mobility of one of the constituent organic materials of the OLED.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] In these, exciplex emission is often reported to be redshifted with respect to the bulk EL emission. 10,12 This is related to the energy difference between the highest occupied molecular orbital ͑HOMO͒ level ͑ionization potential͒ of the hole transporting material and the lowest-unoccupied molecular orbital ͑LUMO͒ level ͑electron affinity͒ of the electron transporting material, which favors generation of bound states of lower energy rather than excitons.…”
Section: Introductionmentioning
confidence: 99%